Preparation and Characterization of New Metal Complexes of Schiff Bases Contaning a Thiazole Ring - Abdul-Ghani, Ahlam; Majeed, R. (Iraqi Journal of Science, 2025)
New metal Complexes of two newly prepared Schiff bases (Ly and Ly) and three previously prepared Schiff bases HL, L, Liv by reacting 2-amino benzothiazole(2- ABT) with 2,4-dimethoxybenzaldehyde, salicylaldehyde, 4-hydroxy benzaldehyde, N,N-dimethyl-4-aminobenzaldehyde and from reaction of 2-aminothiazole (2-AT) with 2,4-dintethoxy benzaldehyde respectively. Structures were proposed depending on elemental and thermal analyses (TG and DTG) and by ir and u.v- visible spectra in addition to magnetic susceptibility and electrical conductivity measurements. Some of these compounds exhibited growth inhibition against two types of bacteria.